2013
DOI: 10.1016/j.cma.2012.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Large scale parameter estimation problems in frequency-domain elastodynamics using an error in constitutive equation functional

Abstract: This paper presents the formulation and implementation of an Error in Constitutive Equations (ECE) method suitable for large-scale inverse identification of linear elastic material properties in the context of steady-state elastodynamics. In ECE-based methods, the inverse problem is postulated as an optimization problem in which the cost functional measures the discrepancy in the constitutive equations that connect kinematically admissible strains and dynamically admissible stresses. Furthermore, in a more rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 31 publications
3
74
0
Order By: Relevance
“…Like in earlier applications of MECE to parameter identification, e.g. [5, 3], this subdivision makes it natural to adopt an iterative alternating strategy of block Gauss-Seidel type whereby each solution iteration for (21) consists in (i) solving the set of linear equations (21a)–(21d) for the mechanical fields and Lagrange multipliers, with kept fixed, and (ii) updating via equation (21e). Here, this method will be seen to entail solving a 4 × 4 complex symmetric block linear system followed (when considering isotropic materials) by simple and explicit update formulas for the elastic moduli, similar to those used in [3].…”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Like in earlier applications of MECE to parameter identification, e.g. [5, 3], this subdivision makes it natural to adopt an iterative alternating strategy of block Gauss-Seidel type whereby each solution iteration for (21) consists in (i) solving the set of linear equations (21a)–(21d) for the mechanical fields and Lagrange multipliers, with kept fixed, and (ii) updating via equation (21e). Here, this method will be seen to entail solving a 4 × 4 complex symmetric block linear system followed (when considering isotropic materials) by simple and explicit update formulas for the elastic moduli, similar to those used in [3].…”
Section: Formulationmentioning
confidence: 99%
“…More recent extensions of the MECE approach to time-domain formulations [2,16] were shown to be very robust in the presence of high levels of noise, while also providing an inherent error estimate through the ECE. The MECE method was extended to large scale identification problems in [3], where the authors also showed that this approach displayed fast convergence and accuracy as compared to conventional least-squares minimization approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In this case it is considered an error included directly in the displacements vector by using the procedure applied in [5,43]. The results obtained in this work and in the papers cited are not directly comparable since more than one displacement field is used, thus a different MIP is solved.…”
Section: Results For Interpolation Error In Umentioning
confidence: 94%
“…The geometry considered in this case also corresponds to a problem usually used in the literature [5]. We start by describing the problem, and after that, we present the results obtained when different kinds of errors are introduced in the data.…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation